Pengaruh Kualitas Pelayanan, Ketepatan Waktu, Dan Tarif Pengiriman Terhadap Kepuasan Pelanggan PT. POS INDONESIA (Studi Kasus Pada Pelanggan PT. POS INDONESIA Cabang Gempol) - Shintia Juniariska; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to examine the effect simultaneously and partially between service quality, timeliness and shipping rates on customer satisfaction PT. Indonesian post.The population in this study are customers of PT. Pos Indonesia, which amounted to 12,000 while the sample of this study using a purposive sampling method is a customer based on the criteria of respondents PT. Pos Indonesia as many as 100 respondents, with a sampling technique using a questionnaire and the analysis used in this study is quantitative analysis, with the type of explanatory research. By using the simultaneous test (Test F), partially (Test T) which is assisted by SPSS 16 For Windows software.Overall results of multiple linear regression analysis and hypothesis testing can be concluded that simultaneously (Test F) service quality, timeliness and shipping rates have a significant effect on customer satisfaction of PT.Pos Indonesia, partially (T test) service quality, timeliness and tariff delivery has a significant effect on customer satisfaction PT. Pos Indonesia. Keywords: customer satisfaction, service quality, timeliness, shipping rates